Utilizing flat-panel detector parenchymal blood volume imaging (FD-PBV) for quantitative kidney perfusion analysis during the process of percutaneous transluminal renal angioplasty (PTRA): A case report. Issue 47 (November 2017) - Qiu, Chenyang; Shao, Jiang; Liu, Xiu; Liu, Bao
Abstract: Rationale: Traditional digital subtraction angiography (DSA) provides lumen morphology of renal artery as indicators for vascular patency in patients with renal artery stenosis (RAS). It, however, lacks hemodynamic information toward target kidney. To solve this shortcoming, a novel technique, flat-panel detector parenchymal blood volume imaging (FD-PBV), is introduced, which is able to evaluate hemodynamic changes of target kidney intraoperatively. Patients concerns: A 77-year-old female presented with hypertension, intermittent dizziness, nausea, and fatigue. Diagnoses: Ninety-nine percent stenosis of left RAS was found. Interventions: Percutaneous transluminal renal angioplasty was performed, along with FD-PBV acquisition protocol. Outcomes: Her symptoms relieved gradually after procedure. Intuitive FD-PBV maps showed her renal perfusion improved remarkably. Quantitative analysis of FD-PBV showed her kidney volume was 47.02 and 75.61 cm 3 with average density of contrast medium (CM) 58.1 HU and 311.5 HU before and after stenting. Follow-up at 6 months showed patency of the stent and stable kidney blood perfusion. Lessons: FD-PBV technique possesses a remarkable value in quantitatively assessing the changes of kidney blood perfusion and can be a useful auxiliary technique for DSA.